The Metabotropic Glutamate Receptor Subtype 5 (mGluR5) Mediates Sensitivity to the Sedative Properties of Ethanol - Downing, Chris (2010)
OBJECTIVE: Inbred Long-Sleep and Short-Sleep mice (ILS and ISS) were selectively bred for differential sensitivity to the sedative effects of ethanol. Lines of mice derived from these progenitors have been used to identify several Quantitative Trait Loci (QTLs) mediating Loss Of the Righting reflex due to Ethanol (LORE). The present study investigated mGluR5 as a candidate gene underlying Lore7, a QTL mediating differential LORE sensitivity. METHODS: We used knockout mice, a quantitative complementation test, pharmacological antagonism of mGluR5, real-time quantitative PCR, radioligand binding, DNA sequencing and bioinformatics to examine the role of mGluR5 in ethanol-induced sedation. RESULTS: mGluR5 knockout mice had a significantly longer LORE duration than wild-type controls. Administration of the mGluR5 antagonist 2-methyl-6-(phenylethyl)-pyridine (MPEP) had differential effects on LORE in ILS and ISS mice. A quantitative complementation test also supported mGluR5 mediating LORE. Two intronic single-nucleotide polymorphisms in mGluR5 were highly correlated with LORE in recombinant inbred mice derived from a cross between ILS and ISS (LXS RIs). Differences in mGluR5 mRNA level and receptor density were observed between ILS and ISS in distinct brain regions. Finally, data from WebQTL showed that mGluR5 expression was highly correlated with several LORE phenotypes in the LXS RIs. CONCLUSIONS: Taken together, this data provides convincing evidence that mGluR5 mediates differential sensitivity to the sedative effects of ethanol. Studies from the human literature have also identified MGLUR5 as a potential candidate gene for ethanol sensitivity.